Online Sexual Harassment Perpetration Among Peer Adolescents: A Cross-National and Cross-Gender Study - Estrella Durán-Guerrero; Annalaura Nocentini; Ersilia Menesini; Virginia Sánchez-Jiménez (Behavioral Sciences, 2025)
This study aims to validate the Online Sexual Harassment Perpetration among Peers (OSHP-P) instrument for assessing online sexual harassment among adolescents in two different countries, Spain and Italy, considering both new forms of online sexual harassment and gender differences. The instrument was validated by means of a Confirmatory Factor Analysis (CFA) with a sample of 1041 Spanish (Mage = 15.0, SD = 0.88) and 1385 Italian (Mage = 14.8, SD = 0.87) adolescents, demonstrating factorial invariance across both country and gender. The best-fitting model was two-dimensional, with ambiguous and direct Sexual Cyber Perpetration (SCP) and Non-Consensual Sharing Perpetration (NCSP) factors. Co-involvement (i.e., involvement in both types of aggression) rates were 10.3% in Spain and 7.8% in Italy. No significant gender differences were found for involvement in either the overall scale (46.4% for girls, 44.1% for boys) or the NCSP subscale (3.0% girls vs. 2.2% boys), although significantly higher co-involvement was found among boys (7.7% girls vs. 10.1% boys). This study contributes to the existing body of research on online sexual harassment among peers in adolescence by presenting a new assessment tool that has been shown to be invariant between Spanish and Italian adolescents, as well as between boys and girls.